Detection of Nausea-Like Response in Rats by Monitoring Facial Expression - Yamamoto, Kouichi; Tatsutani, Soichi; Ishida, Takayuki (Frontiers in Pharmacology, 2017)
Patients receiving cancer chemotherapy experience nausea and vomiting. They are not life-threatening symptoms, but their insufficient control reduces the patients’ quality of life. To identify methods for the management of nausea and vomiting in preclinical studies, the objective evaluation of these symptoms in laboratory animals is required. Unlike vomiting, nausea is defined as a subjective feeling described as recognition of the need to vomit; thus, determination of the severity of nausea in laboratory animals is considered to be difficult. However, since we observed that rats grimace after the administration of cisplatin, we hypothesized that changes in facial expression can be used as a method to detect nausea. In this study, we monitored the changes in the facial expression of rats after the administration of cisplatin and investigated the effect of anti-emetic drugs on the prevention of cisplatin-induced changes in facial expression. Rats were housed in individual cages with free access to food and tap water, and their facial expressions were continuously recorded by infrared video camera. On the day of the experiment, rats received cisplatin (0, 3, and 6 mg/kg, i.p.) with or without a daily injection of a 5-HT3 receptor antagonist (granisetron: 0.1 mg/kg, i.p.) or a neurokinin NK1 receptor antagonist (fosaprepitant: 2 mg/kg, i.p.), and their eye-opening index (the ratio between longitudinal and axial lengths of the eye) in the recorded video image was calculated. Cisplatin significantly and dose-dependently induced a decrease of the eye-opening index 6 h after the cisplatin injection, and the decrease continued for 2 days. The acute phase (day 1), but not the delayed phase (day 2), of the decreased eye-opening index was inhibited by treatment with granisetron; however, fosaprepitant abolished both phases of changes. The time-course of changes in facial expression are similar to clinical evidence of cisplatin-induced nausea in humans. These findings indicate that the monitoring of facial expression has the potential to be useful for the detection of a nausea-like response in laboratory animals.